Use of composition comprising disintegrated starch in complexed form as abrasive and / or structuring agent

By using complexed form of disintegrated starch particles, the environmental micropollution problem caused by traditional plastic microbeads is solved, and the performance is comparable to that of traditional microbeads is achieved.

CN119656065APending Publication Date: 2025-03-21NOVAMONT SPA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411845204.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-01-19
Filing Date
2017-01-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Due to long-term degradation problems, traditional plastic microbeads lead to micropollution in the environment, causing environmental harm, and they need to find alternatives.

Method used

Particles containing complexed form of disassembled starch are used as abrasives and/or structuring agents, which by complexing with the polymer, contain hydrophilic groups inserted from the hydrophobic sequence, form spherical particles for use in cosmetic, dermatology, washing and cleaning formulations.

Benefits of technology

The particles are comparable in performance to traditional microbeads, but have the advantages of rapid biodegradation, do not cause microcontamination, and are of comparable or lower cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189008690000051
    Figure BDA0005189008690000051
  • Figure BDA0005189008690000131
    Figure BDA0005189008690000131
  • Figure BDA0005189008690000141
    Figure BDA0005189008690000141
Patent Text Reader

Abstract

The present invention relates to the use of microparticles comprising disintegrated starch in complexed form as abrasives and / or structuring agents in cosmetic, dermatological, washing and cleansing formulations.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese patent application No. 201780007233.6. The present invention relates to the use of microparticles containing destructurized starch in complex form as abrasives and / or structurants in cosmetic, dermatological, washing and cleaning preparations.

[0002] Abrasives and / or structurants are plastic microparticles (or microbeads) which have long been used to achieve an abrasive effect or to have an aesthetic structuring function in various industrial sectors and in various products, such as cosmetics, dermatology, washing and cleaning preparations.

[0003] Conventional microbeads are mainly based on polyethylene and / or polyamide and, due to the very long degradation times of these polymers, they can lead to the risk of accumulation of microplastics in the environment and in particular in oceans, seas, rivers and lakes. Such microplastics thus contribute to the phenomenon commonly known as "micropollution", i.e. the accumulation of microplastic fragments with very long decomposition times, which are ingested by fish and marine mammals and gradually accumulate in the food chain.

[0004] In view of the increasingly harmful nature of this phenomenon, many initiatives have been launched at national level in many countries and at international level to prevent and gradually eliminate the use of traditional microbeads in various products, including in cosmetics in particular, due to their negative environmental impact.

[0005] Therefore, various industries are particularly interested in finding alternatives to conventional microbeads to overcome the above-mentioned problems.

[0006] Starting from this technical problem, it has now been surprisingly found that, by using a composition comprising disintegrated starch in complex form, it is possible to obtain, during use, properties completely similar to those achievable with conventional microbeads, while the cost is at least comparable to that of conventional microbeads, if not lower, and it also has the advantage of being rapidly biodegradable and therefore not causing microfouling.

[0007] The present application therefore relates to the use of microparticles as abrasives and / or structurants, the microparticles comprising decomposed starch in complex form with a polymer comprising hydrophilic groups intercalated by hydrophobic sequences, the microparticles being particularly suitable for cosmetic, dermatological, washing and cleaning preparations.

[0008] The term "structurant" as used herein refers to an ingredient that improves softness, smoothness, absorption rate and film-forming properties when added to aqueous or lipophilic formulations such as emulsions. Alternatively, the term "structurant" as used herein refers to an ingredient that improves slip, smoothness and matte properties when added to anhydrous formulations. These properties are tested by sensory analysis.

[0009] In fact, the use of decomposed starch in complex form with a polymer comprising hydrophilic groups intercalated by hydrophobic sequences makes it possible to obtain microparticles in the form of spherical particles preferably with a diameter between 1 and 1000 μm with a grinding and / or structuring effect, which cannot be obtained in other ways, for example by using starch that still has its native granular structure or in any case is not in complex form.

[0010] In the meaning of the present invention, degraded starch refers in fact to any type of starch that has lost its native granular structure. With regard to the native granular structure of the starch, this can advantageously be identified by phase contrast optical microscopy. In a particularly preferred embodiment of the present invention, degraded starch is a starch that has completely lost its native granular structure, also referred to as "completely degraded starch starch".

[0011] The disintegration of starch is advantageously carried out in any equipment capable of providing temperature, pressure and shear conditions suitable for destroying the natural granular structure of starch. For example, European patents EP-0 118 240 and EP-0 327 505 disclose conditions suitable for obtaining complete disintegration of starch. Advantageously, the starch is disintegrated by an extrusion process at a temperature of 110-250° C., preferably 130-180° C., preferably at a pressure of 0.1-7 MPa, preferably 0.3-6 MPa, and preferably provides a specific energy of more than 0.1 kWh / kg during the extrusion process.

[0012] In the definition of the present invention, the disintegrated starch in complexed form with a polymer comprising hydrophilic groups inserted by hydrophobic sequences refers to disintegrated starch that has formed one or more supramolecular structures, which can be detected by X-ray spectrometry ( Cu K α X-ray) and exists in one or more crystalline forms, which can be associated with one or more diffraction peaks listed below.

[0013] The present invention also relates to the following embodiments:

[0014] 1. Use of microparticles comprising decomposed starch in complexed form with a polymer comprising hydrophilic groups intercalated by hydrophobic sequences as abrasives and / or structurants in cosmetic, dermatological, washing and cleaning preparations.

[0015] 2. The use according to embodiment 1, wherein the microparticles comprise, relative to the total amount of components i-iv:

[0016] i. 30-80% disintegrated starch;

[0017] ii. 20-70% of the polymer comprises hydrophilic groups inserted by hydrophobic sequences;

[0018] iii. 0-25% plasticizer;

[0019] iv. 0-50% water.

[0020] 3. The use according to any one of embodiments 1 to 2, wherein the polymer comprising hydrophilic groups intercalated by hydrophobic sequences is selected from:

[0021] - polyvinyl alcohol having a degree of hydrolysis of 10 to 100%;

[0022] - vinyl alcohol / vinyl acetate block copolymers;

[0023] - polyvinyl acetate in dry form and in emulsified form in water;

[0024] - copolymers of ethylene with vinyl alcohol, vinyl acetate, acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic anhydride, glycidyl methacrylate and mixtures thereof;

[0025] - aliphatic 6-6, 6-9 or 12 polyamides, aliphatic polyurethanes, aliphatic and aliphatic / aromatic polyesters, polyurethane / polyamide, polyurethane / polyether, polyurethane / polyester, polyamide / polyester, polyamide / polyether, polyester / polyether, polyurea / polyester, polyurea / polyether, polylactic acid, polyglycolic acid, polycaprolactone / polyurethane random and block copolymers, wherein the molecular weight of the polycaprolactone block is 300-3000.

[0026] 4. The use according to embodiment 3, wherein the polymer comprising hydrophilic groups intercalated by hydrophobic sequences is polyvinyl alcohol having a degree of hydrolysis of 10-100%.

[0027] 5. The use according to embodiment 3, wherein the polymer comprising hydrophilic groups interrupted by hydrophobic sequences is a vinyl alcohol / vinyl acetate block copolymer.

[0028] 6. Use according to embodiment 3, wherein the polymer comprising hydrophilic groups interrupted by hydrophobic sequences is polyvinyl acetate.

[0029] 7. The use according to embodiment 3, wherein the polymer comprising hydrophilic groups intercalated by hydrophobic sequences is a copolymer of ethylene with vinyl alcohol and / or acrylic acid.

[0030] 8. Use according to embodiment 7, wherein the copolymer of ethylene and vinyl alcohol contains 20 to 50 mol % of ethylene units.

[0031] 9. The use according to embodiment 7, wherein the copolymer of ethylene and acrylic acid contains 70 to 99% by weight of ethylene units.

[0032] 10. Cosmetic, dermatological, washing and cleaning preparations comprising as abrasive and / or structurant microparticles comprising decomposed starch in complexed form with a polymer comprising hydrophilic groups intercalated by hydrophobic sequences.

[0033] 11. Cosmetic, dermatological, washing and cleaning preparations according to embodiment 10, comprising 1 to 20% by weight of said microparticles as abrasive and / or structurant, relative to the total weight of the preparation.

[0034] 12. The cosmetic, dermatological, washing and cleaning formulation according to any one of embodiments 10 to 11, wherein the microparticles comprise, relative to the total weight of components i-iv:

[0035] i. 30-80% disintegrated starch;

[0036] ii. 20-70% of the polymer comprises hydrophilic groups inserted by hydrophobic sequences;

[0037] iii. 0-25% plasticizer;

[0038] iv. 0-50% water.

[0039] 13. The cosmetic, dermatological, washing and cleaning formulation according to any one of embodiments 10 to 12, wherein the polymer comprising hydrophilic groups interspersed by hydrophobic sequences is chosen from:

[0040] - polyvinyl alcohol having a degree of hydrolysis of 10 to 100%;

[0041] - vinyl alcohol / vinyl acetate block copolymers;

[0042] - polyvinyl acetate in dry form and in emulsified form in water;

[0043] - copolymers of ethylene with vinyl alcohol, vinyl acetate, acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic anhydride, glycidyl methacrylate and mixtures thereof;

[0044] - aliphatic 6-6, 6-9 or 12 polyamides, aliphatic polyurethanes, aliphatic and aliphatic / aromatic polyesters, polyurethane / polyamide, polyurethane / polyether, polyurethane / polyester, polyamide / polyester, polyamide / polyether, polyester / polyether, polyurea / polyester, polyurea / polyether, polylactic acid, polyglycolic acid, polycaprolactone / polyurethane random and block copolymers, wherein the molecular weight of the polycaprolactone block is 300-3000.

[0045] 14. The cosmetic, dermatological, washing and cleaning formulation according to embodiment 13, wherein the polymer comprising hydrophilic groups interspersed by hydrophobic sequences is a polyvinyl alcohol having a degree of hydrolysis of 10-100%.

[0046] 15. The cosmetic, dermatological, washing and cleaning formulation according to embodiment 13, wherein the polymer comprising hydrophilic groups interrupted by hydrophobic sequences is a vinyl alcohol / vinyl acetate block copolymer.

[0047] 16. The cosmetic, dermatological, washing and cleaning formulation according to embodiment 13, wherein the polymer comprising hydrophilic groups interrupted by hydrophobic sequences is polyvinyl acetate.

[0048] 17. Cosmetic, dermatological, washing and cleaning preparations according to embodiment 13, wherein the polymer comprising hydrophilic groups interrupted by hydrophobic sequences is a copolymer of ethylene with vinyl alcohol, vinyl acetate and / or acrylic acid.

[0049] 18. The cosmetic, dermatological, washing and cleaning preparation according to embodiment 17, wherein the copolymer of ethylene and vinyl alcohol contains 20 to 50 mol % of ethylene units.

[0050] 19. The cosmetic, dermatological, washing and cleaning preparation according to embodiment 17, wherein the copolymer of ethylene and acrylic acid contains 70 to 99 mol % of ethylene units.

[0051]

[0052] In a preferred embodiment, the microparticles according to the invention comprise, relative to the total weight of components i-iv:

[0053] i. 30-80% disintegrated starch;

[0054] ii. 20-70% of the polymer comprises hydrophilic groups inserted by hydrophobic sequences;

[0056] iii. 0-25% plasticizer;

[0057] iv. 0-50% water.

[0058] The starch that can be used to prepare the disintegrated starch of the present invention is preferably selected from natural starch (for example, such as corn starch, potato starch, rice starch, tapioca starch), oxidized starch, dextrinized starch, etherified starch (such as preferably starch ethoxylate, starch silyl ether), starch ester (for example preferably starch hydroxypropylate, starch acetate) and mixtures thereof. The starch that is preferably used to prepare the disintegrated starch is natural starch.

[0059] In one embodiment, the present invention relates to the use of microparticles comprising one or more "silyl ethers of disintegrated starch" as abrasives and / or structurants, and this term refers to disintegrated starch wherein at least one oxygen atom in the disintegrated starch is covalently bonded to at least one silicon atom and / or to at least one silicon-containing compound.

[0060] As for the silicon-containing compounds, they are preferably selected from organosilanes, including organodisilanes, organotrisilanes, organopolysilanes, halosilanes, including di-, tri- and polyhalosilanes, silanols, including di-, tri- and polysilanols, and silazanes, including di-, tri- and polysilazanes. More preferably, the silicon-containing compounds are selected from organosilanes, and even more preferably from those having the following general formula:

[0061] (RO)3SiC n H 2n+1 (I)

[0062] (RO)3SiC n H 2n X (II)

[0063] (RO)3SiC n H 2n S m Y (III)

[0064] (RO)3SiC n H 2n S m C n H 2n Si(OR)3 (IV)

[0065] wherein R represents an alkyl group having 1 to 4 carbon atoms, and the Rs are the same as or different from each other;

[0066] "n" represents an integer from 1 to 12;

[0067] "m" represents an integer from 1 to 6;

[0068] X represents a thiol group, an amine group, a vinyl group, a nitroso group, an imide group, a chlorine atom or an epoxy group;

[0069] Y represents a cyano group, an N,N-dimethylthiocarbamoyl group, a mercaptobenzotriazolyl group or a methacrylate group.

[0070] Sulfur-free organosilanes are particularly preferred.

[0071] As far as the silyl ethers of degraded starch are concerned, these can be obtained by a single-stage process or in several stages. In a first preferred embodiment, degraded starch silyl ethers are obtained by subjecting one or more silyl ethers of starch to temperature, pressure and shear conditions suitable for destroying the natural granular structure of the starch, according to the teachings relating to the degrading process shown above.

[0072] Alternatively, the silyl ether of disintegrated starch is preferably obtained by mixing the already disintegrated starch with at least one silicon-containing compound at a temperature of 110-250° C., preferably 130-180° C. Mixing can be carried out in any equipment suitable for this purpose, preferably in a static mixer or an extruder, more preferably in an extruder. During the preparation of the silyl ether of disintegrated starch according to the invention, the silicon-containing compound can be overdosed relative to the starch, or in any case not cause a complete reaction with the latter, so that the silyl ether of disintegrated starch according to the invention can advantageously contain 1 to 20% by weight of at least one silicon-containing compound, preferably an organosilane, a halosilane, a silanol and a silazane that is not bound to the oxygen atoms of starch. More preferably, the silicon compound that is not connected to the oxygen atoms of starch is an organosilane.

[0073] As far as polymers comprising hydrophilic groups interrupted by hydrophobic sequences are concerned, these are advantageously chosen from:

[0074] i. a polyvinyl alcohol having a degree of hydrolysis of 10 to 100%, preferably between 70 and 99%;

[0075] ii. vinyl alcohol / vinyl acetate block copolymer;

[0076] iii. polyvinyl acetate in dry form or in the form of emulsification in water;

[0077] iv. Ethylene and vinyl alcohol, vinyl acetate, acrylic acid, methacrylic acid, croton

[0078] Acid, itaconic acid, maleic anhydride, glycidyl methacrylate and mixtures thereof

[0079] Copolymers of substances;

[0080] v.6-6, 6-9 or 12 aliphatic polyamide, aliphatic polyurethane, aliphatic and aliphatic / aromatic

[0081] Polyester, polyurethane / polyamide, polyurethane / polyether, polyurethane / polyester,

[0082] Polyamide / polyester, polyamide / polyether, polyester / polyether, polyurea / polyester, poly

[0083] Urea / polyether, polylactic acid, polyglycolic acid, polycaprolactone / polyurethane random or

[0084] The block copolymer has a molecular weight of 300-3000 in the polycaprolactone block.

[0085] Mixtures of the polymers mentioned may also be used.

[0086] Among the polymers comprising hydrophilic groups interrupted by hydrophobic sequences, preferred are copolymers of ethylene with vinyl alcohol and / or acrylic acid, polyvinyl alcohol having a degree of hydrolysis of from 10 to 100%, polyvinyl acetate in dry form or in emulsified form in water, vinyl alcohol / vinyl acetate block copolymers and mixtures thereof.

[0087] Among these, particularly preferred are copolymers of ethylene with vinyl alcohol and / or acrylic acid and polyvinyl alcohol having a degree of hydrolysis of 10-100%. Even more preferably, polyvinyl alcohol having a degree of hydrolysis of 70-99% is used as the polymer comprising hydrophilic groups intercalated by hydrophobic sequences.

[0088] In the case of copolymers of ethylene and vinyl alcohol, the latter preferably contains from 20 to 50 mol % of ethylene units.

[0089] In the case of copolymers of ethylene and acrylic acid, these preferably contain 70 to 99% by weight of ethylene units.

[0090] As far as plasticizers are concerned, these are preferably chosen from polyols having 2 to 22 carbon atoms. Among the polyols, preferred ones are polyols having 1 to 20 hydroxyl groups with 2 to 6 carbon atoms, their ethers, thioethers and organic and inorganic esters. Examples of polyols are glycerol, diglycerol, polyglycerol, pentaerythritol, polyglycerol ethoxylates, ethylene glycol, polyethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, neopentyl glycol, sorbitol monoacetate, sorbitol diacetate, sorbitol monoethoxylate, sorbitol diethoxylate, and mixtures thereof. In a preferred embodiment, the plasticizer comprises glycerol or a plasticizer mixture comprising glycerol, more preferably comprising 2-90% by weight of glycerol relative to the total weight of the plasticizer.

[0091] As regards water, this may also be that which is naturally present in the starch. In addition to components i-iv, the microparticles according to the invention may also comprise further additives, such as fillers, dispersants, crosslinkers, surfactants, defoamers, suspending agents, thickeners, preservatives, pigments and colorants.

[0092] As far as fillers are concerned, these can be inorganic and / or organic. Examples of particularly preferred inorganic fillers are: talc, clay, silica, mica, kaolin, titanium dioxide and wollastonite. Preferred organic fillers are those derived from raw materials of renewable origin, such as cellulose fibers.

[0093] Surfactant is advantageously selected from anionic, cationic and nonionic surfactants. Cationic surfactants generally contain bulky cations, which generally contain long alkyl chains (e.g., quaternary ammonium salts, phosphonium salts or sulfonium salts). In most cases, anions are chloride ions, sulfate ions or nitrate ions. Anionic surfactants generally include alkyl, aryl, alkylaryl, styryl, di- or tristyryl sulfonates, sulfates, phosphates, phosphonates, dithiocarbamates or carboxylates, which are generally neutralized with alkali or alkaline earth metals, amines and alkanolamines.

[0094] Examples of nonionic surfactants include products belonging to the classes of polyethoxylated esters and ethers, alkyl polyglucosides, sorbitol and sucrose derivatives, fatty acid esters or amides, fatty amine mono- and diglycerides, ethoxylated alkylphenols, di- or tristyrylphenyl ethoxylates or ethoxy-propoxylate block copolymers.

[0095] Examples of defoamers include silicone defoamers and fatty acid salts. If desired, pigments and colorants or color stabilizers such as titanium dioxide, clay, calcium carbonate, talc, mica, silicon dioxide, silicates, iron oxides and hydroxides, carbon black and magnesium oxide may also be added.

[0096] The microparticles according to the invention comprising the decomposed starch in complexed form with a polymer comprising hydrophilic groups intercalated by hydrophobic sequences can be prepared by a process comprising one or more stages of mixing the components, said mixing preferably being carried out by extrusion. Suitable extruders for the mixing stage according to the invention are both single and twin screw extruders, preferably equipped with screws having a profile with high mixing capacity (for example the presence of "reverse" elements).

[0097] In a first embodiment, the microparticles according to the invention are prepared by a single-stage process comprising mixing the components and wherein the disintegration of the starch is carried out in the presence of a polymer comprising hydrophilic groups intercalated by hydrophobic sequences, preferably in the presence of one or more plasticizers such as those mentioned above and / or water, said water being advantageously naturally present in the starch, by an extrusion process preferably at a temperature of 110-250° C. and more preferably between 130-210° C. and providing during said extrusion a specific energy preferably greater than 0.1 kWh / kg.

[0098] In a preferred embodiment of the process comprising a single mixing stage, the microparticles according to the invention can then be obtained by a process providing a one-stage mixing process, wherein:

[0099] a. A composition comprising 20 to 90% by weight of at least one native starch, 10 to 80% by weight of at least one polymer comprising hydrophilic groups inserted by hydrophobic sequences, 0 to 40% by weight of one or more plasticizers, preferably comprising at least 2-90% by weight of glycerol relative to the total weight of plasticizers, 0-40% by weight of water, extruded at a temperature of 110-250° C., preferably 130-210° C., and providing a specific energy preferably greater than 0.1 kWh / kg.

[0100] In another embodiment, the polymer comprising hydrophilic groups intercalated by hydrophobic sequences and any other components can also be added after the disintegration of the starch. According to this embodiment, the microparticles according to the invention can then be obtained by a process providing two mixing stages, wherein:

[0101] a. extruding at least one native starch at a temperature of 110-250° C., preferably 130-180° C., preferably in the presence of 0-40% by weight of one or more plasticizers relative to the weight of the native starch, the one or more plasticizers preferably comprising at least 2-90% by weight of glycerol, relative to the total weight of the plasticizers, and providing a specific energy preferably greater than 0.1 kWh / kg, and

[0102] b. A composition comprising 30-90% by weight of the disintegrated starch obtained in stage a, 10-70% by weight of at least one polymer comprising hydrophilic groups inserted by hydrophobic sequences, 0-40% by weight of one or more plasticizers, which preferably comprises at least 2-90% by weight of glycerol relative to the total weight of plasticizers, 0-40% by weight of water, extruded at a temperature of 110-250° C., preferably 130-210° C., and providing a specific energy preferably greater than 0.1 kWh / kg.

[0103] The preparation of the microparticles according to the invention preferably provides, after the components have been mixed, a grinding process in order to obtain spherical particles having a diameter between 1 and 100 μm, preferably between 1 and 60 μm.

[0104] The milling process provides for a step of cryogenically grinding the complex starch in order to pre-reduce the size of the particles to a diameter of less than 1 mm and subsequent jet mill milling to obtain the desired size.

[0105] The diameter of the spherical particles is determined according to standard ISO 13320 using a laser particle sizer.

[0106] Preferably, the microparticles according to the invention are used as abrasives and / or structurants in cosmetic, dermatological, washing and cleaning preparations.

[0107] According to another embodiment, the present invention is directed to the use of microparticles in laser sintering applications.

[0108] Cosmetic, dermatological, washing and cleaning preparations preferably comprise up to 20% by weight, more preferably from 1 to 10% by weight, even more preferably from 2 to 5% by weight, of microparticles as abrasives and / or structurants according to the invention, the microparticles comprising decomposed starch in complex form with a polymer comprising hydrophilic groups intercalated by hydrophobic sequences, the percentages relating to the total weight of the respective preparation.

[0109] Preferably, due to the use of the microparticles according to the invention, the cosmetic, dermatological, washing and cleaning formulations have optimal sensory properties in terms of flowability, and / or optimal stability properties, for example as determined by no noticeable changes in pH, viscosity, color, odor or appearance, even after six months.

[0110] The cosmetic, dermatological, washing and cleaning preparations according to the invention are preferably in the form of fluids, gels, foams, sprays, lotions or creams. The preparations are preferably formulated in the form of aqueous or lipophilic preparations, such as emulsions (e.g. basic creams and bases), solutions or dispersions, or anhydrous preparations (e.g. lipsticks). The preparations according to the invention are preferably in the form of water-in-oil and oil-in-water emulsions.

[0111] The microparticles of the invention may be added to the formulation in the form of an aqueous dispersion by any means known to those skilled in the art.

[0112] The preparations may also contain other additives and auxiliaries commonly used in the corresponding application fields, such as oils, waxes, surfactants, suspending agents, preservatives, emulsifiers, co-emulsifiers, dispersants, surfactants, polymers, defoamers, solubilizers, stabilizers, film formers, thickeners, gelling agents, softeners, disinfectants, active ingredients, astringents, deodorants, sunscreens, antioxidants, oxidants, wetting agents, solvents, colorants, pigments, textile agents, fragrances, sunscreens and / or silicones. In particular, the plant health product also contains one or more phytomedicines.

[0113] In a preferred embodiment, the microparticles according to the invention have a biodegradability determined according to standard EN 13432 of at least 55%, preferably 60%, more preferably 70%.

[0114] In another preferred embodiment, the microparticles according to the invention are biodegradable when composted in the sense of standard EN 13432.

[0115] The present invention will now be described using some examples which are to be considered as illustrative rather than limiting.

[0116] Example 1

[0117] 49.5 parts of native corn starch (containing 12% by weight of water), 32.2 parts of polyvinyl alcohol having a degree of hydrolysis of 88%, 7 parts of glycerol and 11.2 parts of water were fed to a TSA twin-screw extruder set at the following operating parameters:

[0118] Temperature profile

[0119] Feeding area (℃): 60

[0120] Extrusion zone (℃): 120-200×4-110-90

[0121] Production capacity (kg / h) = 3

[0122] SME (specific energy) (kWh / kg) = 0.267

[0123] The composition thus obtained was ground and sieved to a particle size of <250 μm at 25° C. and used in a Philips X'Pert θ / 2θ X-ray spectrometer with Bragg-Brentano geometry. and Cu K with a power of 1.6 kW α The analysis was performed with X-ray radiation. The angular range used was from 5 to 60° (2θ) with a step size of 0.03° (2θ) and an acquisition time of 2 seconds per step.

[0124] Spectral analysis showed that there were diffraction peaks at 2θ = 12.7-16.5-18.2-19.4-22.0, indicating that a complex (V H form).

[0125] The compositions were analyzed using optical microscopy using a Leitz Wetzlar Orthoplan model phase contrast microscope adjusted to the following parameters:

[0126] Magnification 400X

[0127] EF 40 / 0.65 Phaco 2 objective lens

[0128] Phase ring number 5

[0129] The composition showed no remnants of granular structure attributable to the presence of starch, thus revealing the disintegrated nature of the starch.

[0130] The composition was then ground by grinding in a pin crusher in the presence of liquid nitrogen to produce a powder of size <1 mm. The powder was further ground by jet mill technology to obtain two types of microparticles in the form of spherical particles with an average diameter of 9 microns (Dv90 = 16 microns) and 12 microns (Dv90 = 21 microns).

[0131] Example 2

[0132] 56.3 parts of native corn starch (containing 12% by weight of water), 24.8 parts of polyethylene acrylic acid containing 20% ​​by weight of acrylic acid, 7.9 parts of glycerol and 10.1 parts of water were fed to an OMC twin-screw extruder set at the following operating parameters:

[0133] Temperature profile

[0134] Feeding area (℃): 60

[0135] Extrusion zone (℃): 145-170-180×4-150×2

[0136] Production capacity (kg / h) = 40

[0137] SME (specific energy) (kWh / kg) = 0.232

[0138] The composition thus obtained was ground and sieved to a particle size of <250 μm at 25° C. and used in a Philips X'Pert θ / 2θ X-ray spectrometer with Bragg-Brentano geometry. and Cu K with a power of 1.6 kW α The analysis was performed with X-ray radiation. The angular range used was from 5 to 60° (2θ) with a step size of 0.03° (2θ) and an acquisition time of 2 seconds per step.

[0139] Spectral analysis showed that there were diffraction peaks at 2θ = 6.8-11.8-13.1-18.1-20.7, indicating that a complex (E H and V A form).

[0140] The compositions were analyzed using optical microscopy of a Leitz Wetzlar Orthoplan type phase contrast microscope adjusted to the following parameters:

[0141] Magnification 400X

[0142] EF 40 / 0.65 Phaco 2 objective lens

[0143] Phase ring number 5

[0144] The composition showed the absence of residues attributable to the granular structure of the starch, thus revealing the disintegrated nature of the starch.

[0145] The composition was then ground by grinding in a pin crusher in the presence of liquid nitrogen to produce a powder of size <1 mm. The powder was further ground by jet mill technology to obtain two types of microparticles in the form of spherical particles with an average diameter of 9 microns (Dv90 = 16 microns) and 12 microns (Dv90 = 21 microns).

[0146] The microparticles were subsequently used as a replacement for conventional microbeads to produce several cosmetic formulations, such as base creams (Examples 3-6) and foundations (Examples 7-10).

[0147] Examples 3 (comparative), 4 (comparative), 5, 6: basic cream formulations.

[0148] Different base cream formulations were prepared and the compositions are reported in Table 1. For each cosmetic formulation, the ingredients are listed according to INCI nomenclature and the amount of each ingredient refers to the total weight of the formulation.

[0149] Table 1

[0150]

[0151]

[0152] Manufacturing method:

[0153] Heat the components of phase A and phase B separately at 65° C. with stirring. Subsequently, phase B is added to phase A with mixing and kept under these conditions for 5 minutes. After cooling to room temperature, phases C and D are added to the mixture with stirring.

[0154] The stability of the base cream formulations according to Examples 3-6 was tested at 25°C for 6 months (Table 2). No significant changes in color, odor, appearance, pH, viscosity were observed, confirming the stability of all formulations.

[0155] The viscosity was measured with the aid of a Brookfield viscometer (RV) equipped with spindle n. 4 at 50 rpm and 25°C.

[0156] Table 2

[0157]

[0158] The formulations prepared according to Examples 3-6 were tested for their softness, smoothness, oiliness, stickiness, film formation and absorption rate by a panel of 20 volunteers (both male and female). Sensory analysis, determined 3 minutes after application, was classified according to the following scale:

[0159] 1 = Definitely not good

[0160] 2 = bad

[0161] 3 = Good enough

[0162] 4 = Good

[0163] 5 = Very good.

[0164] The results are reported in Table 3.

[0165] Table 3 - Group Test

[0166] Example Softness Smoothness Oily viscosity Film forming properties Absorption rate 3(Comparison) 4 4 5 5 3 3 4 (Comparison) 5 4 5 5 4 5 5 5 5 5 5 5 5 6 5 5 5 5 5 5

[0167] Three minutes after application, the base cream formulations of the present invention (Examples 5-6) showed improved smoothness and film formation relative to the formulation containing nylon 12 (Comparative Example 4), as well as an overall improvement over the base formulation (Comparative Example 3).

[0168] Examples 7 (comparative), 8 (comparative), 9, 10: Foundation preparations

[0169] Different base formulations were prepared, the compositions are disclosed in Table 4.

[0170] Table 4

[0171]

[0172]

[0173] Manufacturing method:

[0174] Phase A is prepared at 25° C., while phase B is heated at 80° C. Phase C is added to phase B and cooled to 35° C. Phase A is then added very slowly under a turboemulsifier to the mixture of phases B and C. The mixture is then cooled to 25° C. and phase D is added last.

[0175] The base formulations according to Examples 7-10 were tested for 6 month stability at 25°C (Table 5).

[0176] No significant changes in color, odor, appearance, viscosity were observed, confirming the stability of all formulations.

[0177] The viscosity measurements were carried out with the aid of a Brookfield viscometer (RV) equipped with spindle n. 4 at 50 rpm and 25°C.

[0178] Table 5

[0179]

[0180]

[0181] The formulations prepared according to Examples 7-10 were tested by a panel of 20 adults (both males and females) for softness, smoothness, oiliness, stickiness, film formation, and absorption rate.

[0182] Sensory analysis, determined 3 minutes after application, was classified according to the following scale:

[0183] 1 = Definitely not good

[0184] 2 = bad

[0185] 3 = Good enough

[0186] 4 = Good

[0187] 5 = Very good.

[0188] The results are reported in Table 6.

[0189] Table 6 - Group Test

[0190] Example Softness Smoothness Oily viscosity Film forming properties Absorption rate 7 (Comparison) 3 3 5 4 3 3 8(Comparison) 4 4 4 4 4 3 9 5 5 5 5 5 4 10 5 5 5 5 5 4

[0191] The foundation formulations of the present invention (Examples 9-10) show an overall improvement over the base formulation (Comparative Example 7) and the base formulation containing nylon 12 (Comparative Example 8).

[0192] In addition to the advantages reported above, formulations containing microparticles of the invention have a higher biodegradability relative to conventional formulations comprising microparticles.

[0193] The microparticles according to the present invention are effectively used as a replacement for conventional microbeads to produce cosmetic preparations, which have better properties than conventional microbeads.

Claims

1. Use of microparticles as abrasives and / or structurants in cosmetic, dermatological, washing and cleaning preparations, the microparticles comprising decomposed starch in complexed form with a polymer comprising hydrophilic groups inserted by hydrophobic sequences, wherein the polymer comprising hydrophilic groups inserted by hydrophobic sequences is chosen from copolymers of ethylene with vinyl alcohol and / or acrylic acid, polyvinyl alcohol with a degree of hydrolysis of 10 to 100%, polyvinyl acetate in dry form and in emulsified form in water, vinyl alcohol / vinyl acetate block copolymers and mixtures thereof.

2. The use according to claim 1, wherein the microparticles comprise, relative to the total amount of components i-iv: i. 30-80% disintegrated starch; ii. 20-70% of the polymer comprises hydrophilic groups inserted by hydrophobic sequences; iii. 0-25% plasticizer; iv. 0-50% water.

3. The use according to claim 1, wherein the polymer comprising hydrophilic groups intercalated by hydrophobic sequences is polyvinyl alcohol having a degree of hydrolysis of 10-100%.

4. The use according to claim 1, wherein the polymer comprising hydrophilic groups intercalated by hydrophobic sequences is a vinyl alcohol / vinyl acetate block copolymer.

5. Use according to claim 1, wherein the polymer comprising hydrophilic groups intercalated by hydrophobic sequences is polyvinyl acetate.

6. The use according to claim 1, wherein the polymer comprising hydrophilic groups intercalated by hydrophobic sequences is a copolymer of ethylene with vinyl alcohol and / or acrylic acid.

7. The use according to claim 6, wherein the copolymer of ethylene and vinyl alcohol contains 20 to 50 mol % of ethylene units.

8. The use according to claim 6, wherein the copolymer of ethylene and acrylic acid contains 70 to 99% by weight of ethylene units.

9. Use according to any one of claims 1 to 8, wherein the decomposed starch is a starch which has lost its native granular structure.

10. The use according to any one of claims 1 to 9, wherein the cosmetic, dermatological, washing and cleaning compositions comprise from 1 to 20% by weight of said microparticles relative to the total weight of the composition.

11. The use according to any one of claims 1 to 10, wherein the microparticles are in the form of spherical particles having a diameter between 1 and 100 μm.

12. Cosmetic, dermatological, washing and cleaning preparations comprising, as abrasive and / or structuring agent, microparticles comprising decomposed starch in complexed form with a polymer comprising hydrophilic groups intercalated by hydrophobic sequences, the polymer being chosen from copolymers of ethylene with vinyl alcohol and / or acrylic acid, polyvinyl alcohol having a degree of hydrolysis of from 10 to 100%, polyvinyl acetate in dry form and in emulsified form in water, vinyl alcohol / vinyl acetate block copolymers and mixtures thereof.

13. Cosmetic, dermatological, washing and cleaning preparations according to claim 12, comprising from 1 to 20% by weight of said microparticles as abrasive and / or structurant, relative to the total weight of the preparation.

14. The cosmetic, dermatological, washing and cleaning formulation according to any one of claims 12 to 13, wherein the microparticles comprise, relative to the total weight of components i-iv: i. 30-80% disintegrated starch; ii. 20-70% of the polymer comprises hydrophilic groups inserted by hydrophobic sequences; iii. 0-25% plasticizer; iv. 0-50% water.

15. The cosmetic, dermatological, washing and cleaning formulation according to any one of claims 12 to 14, wherein the polymer comprising hydrophilic groups interspersed by hydrophobic sequences is polyvinyl alcohol having a degree of hydrolysis of 10 to 100%.

16. The cosmetic, dermatological, washing and cleaning formulation according to any one of claims 12 to 14, wherein the polymer comprising hydrophilic groups interrupted by hydrophobic sequences is a vinyl alcohol / vinyl acetate block copolymer.

17. The cosmetic, dermatological, washing and cleaning formulation according to any one of claims 12 to 14, wherein the polymer comprising hydrophilic groups interrupted by hydrophobic sequences is polyvinyl acetate.

18. The cosmetic, dermatological, washing and cleaning formulation according to any one of claims 12 to 14, wherein the polymer comprising hydrophilic groups interrupted by hydrophobic sequences is a copolymer of ethylene with vinyl alcohol, vinyl acetate and / or acrylic acid.

19. The cosmetic, dermatological, washing and cleaning preparation according to claim 18, wherein the copolymer of ethylene and vinyl alcohol contains 20 to 50 mol % of ethylene units.

20. The cosmetic, dermatological, washing and cleaning preparation according to claim 18, wherein the copolymer of ethylene and acrylic acid contains 70 to 99 mol % of ethylene units.

21. The cosmetic, dermatological, washing and cleaning formulation according to any one of claims 12 to 20, wherein the microparticles are in the form of spherical particles having a diameter between 1 and 100 μm.

Citation Information

Patent Citations

  • Process for injection moulding starch

    EP0118240A2

  • Polymeric materials made from destructurized starch and at least one synthetic thermoplastic polymeric material

    EP0327505A2